Complaints Management Practices on Service Performance of the Public Sector in Merauke: The Case of Merauke Local Water Company - Syahruddin; Andri Irawan (GoAcademica Research & Publishing, 2022)
Complaint management becomes significant to the community since it serves to satisfy the community's interests in the realm of public service, while for the service provider, it serves as a component for enhancing the service quality system. This study's objective was to identify and analyze complaint management in drinking and clean water services in Merauke Regency using descriptive and qualitative methodologies. Using indicators of timeliness, facilitation, redress, apology, credibility, and attention, the outcomes of complaint management research in drinking and clean water services in Merauke Regency have not been optimal. This is proven by the fact that there are still a number of things that need to be improved, including the fact that the only alternative to receiving indirect complaints is a suggestion box, and the handling is not optimal. Customers' complaints have been handled, as evidenced by PDAM's still-sluggish administration and lack of information dissemination to customers. The quantity of unresolved complaints from customers of drinking and clean water at PDAM Merauke demonstrates that the pace with which personnel handle concerns is still inadequate.